Bubba Ho-tep [videorecording (Blu-Ray)] - Coscarelli, Don; Campbell, Bruce, 1958-; Joyce, Ella, 1954-; Davis, Ossie; Lansdale, Joe R., 1951-
When mysterious deaths plague the Shady Rest retirement home, it's up to an aging, cantankerous Elvis, and a decrepit and black JFK, to defeat a 3,000-year-old-Egyptian mummy with a penchant for sucking human souls.